1998
DOI: 10.1002/(sici)1099-0917(199812)7:4<191::aid-edp181>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Adults' beliefs about children and mathematics: how important is it and how do children learn about it?

Abstract: A series of studies was conducted which focused on US adults' beliefs about the relative importance of acquiring mathematical skills for preschool children and about how children acquire these skills. In Study 1, adults rated general information, reading and social skills as all being more important than mathematical skills. They also claimed that parents have the most influence on preschool children's learning regardless of content area. In Study 2, the parents of kindergarten children also rated reading, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(25 citation statements)
references
References 12 publications
3
21
1
Order By: Relevance
“…It is further proposed that parents' personal experiences will be related to children's early numeracy exposure (e.g., Huntsinger et al 2000;Musun-Miller and Blevins-Knabe 1998). Since it is often the case that parental behavior is consistent with underlying beliefs and expectations (e.g., LeFevre et al 2002), it was expected that those parents who reported positive mathematics experiences may be more capable and willing to share enriched numeracy experiences with their children than those parents with less optimal experiences, thus impacting children's numeracy scores.…”
Section: Exploring Parental Attitudes Experience and Knowledgecontrasting
confidence: 75%
See 2 more Smart Citations
“…It is further proposed that parents' personal experiences will be related to children's early numeracy exposure (e.g., Huntsinger et al 2000;Musun-Miller and Blevins-Knabe 1998). Since it is often the case that parental behavior is consistent with underlying beliefs and expectations (e.g., LeFevre et al 2002), it was expected that those parents who reported positive mathematics experiences may be more capable and willing to share enriched numeracy experiences with their children than those parents with less optimal experiences, thus impacting children's numeracy scores.…”
Section: Exploring Parental Attitudes Experience and Knowledgecontrasting
confidence: 75%
“…Most work in the home numeracy area has relied on parental reports and questionnaire data (e.g., Musun-Miller and Blevins-Knabe 1998;LeFevre et al 2009c); but with demand characteristics and expectations, it is difficult to ascertain whether parental reports are consistent with behavior. This study extends research by tapping directly into parent behavior and asking them to use diaries to record mathematical interactions, and be videotaped during a laboratory play session.…”
Section: Incorporating Behavioral Measuressupporting
confidence: 60%
See 1 more Smart Citation
“…The children whose parents believed in their mathematics abilities had better results in that subject. Perhaps, due to their positive views, parents provided more challenging tasks and opportunities for mathematics problems solving (Musun-Miller & Blevins-Knabe, 1998). Another hypothesis proposed by Aunola et al (2003) is that parents who realistically believe in their children's mathematics abilities are, themselves, proficient in that domain and, therefore, exhibit positive attitudes towards mathematics (Huntsinger, Jose, Liaw, & Ching, 1997).…”
Section: Perceived Parental Support and Students' Engagement In Schoolmentioning
confidence: 99%
“…In this context, in the analysis of the educational status and occupation of the children's parents and the results of the observation evaluations found that there was a significant difference in favor of the children of the families who had high educational status and who were civil servants. The educational level of the family affects the aspects and attitudes toward mathematics and the quality of the mathematical activities offered to the child at home (Clements and Sarama, 2007;Musun-Miller and Blevins-Knabe, 1998). In the study of mathematical achievements of children attending kindergarten by Çelik (2015), the educational levels of parents and the level of income of their families were found to affect children's mathematical achievements.…”
Section: Discussionmentioning
confidence: 77%